Non-conventional constitutional principles of application in administrative law and emphasis on Ecuadorian electoral law - Andrade Ureña , Ricardo Fabricio (2022)
This article reviews different constitutional principles applied in administrative law and focus on those that are uncommon or unconventional (principles that do not emerge from public international law). State procedures observe the fundamental rules that allow citizens to exercise their rights fully, as well the basic rules to make them effective in case they are violated. To elucidate the relationship between the rights that are the object of this study, from learnings in the field of administrative right and from a doctrinal perspective, this paper takes into consideration the application of the principles in public administration (objective qualities such as values, believes, norms). In conclusion, the principles of administrative law, by their own nature, are often confused with constitutional rights, which has incidence in decision-making within the administrative, judicial, or electoral spheres.